2021
DOI: 10.1051/e3sconf/202128402002
|View full text |Cite
|
Sign up to set email alerts
|

The threat of saline lands, for example, in the Republic of Uzbekistan

Abstract: Salinization of land poses a serious threat and harms all industries, including the environment, agriculture, economy, and so on. In this regard, this topic is very relevant today. The object of the research is the agriculture of the Republic of Uzbekistan. The aim of the study is the impact of saline soils on agriculture in the Republic of Uzbekistan. The current state of reclamation systems, the processes of soil salinization and the quality of irrigation water, as well as the features of the manifestation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As a result of years of monitoring, showed that the decrease in vegetation area was also related to the decrease in water content in the area. This, in turn, means that changes in vegetation dynamics are related to changes in the environment [10,[17][18][19][20]. Results of the use of NDVI indices in determining the area covered by vegetation found that the use of this index in quantitative indicators was effective [13].…”
Section: Resultsmentioning
confidence: 99%
“…As a result of years of monitoring, showed that the decrease in vegetation area was also related to the decrease in water content in the area. This, in turn, means that changes in vegetation dynamics are related to changes in the environment [10,[17][18][19][20]. Results of the use of NDVI indices in determining the area covered by vegetation found that the use of this index in quantitative indicators was effective [13].…”
Section: Resultsmentioning
confidence: 99%
“…However, even with high doses of gypsum, it is not possible to achieve the required level of saturation of the soil solution with calcium in the absence of irrigation [25,26]. By displacing sodium from the soil-absorptive complex with calcium or other divalent or trivalent cations, the mobility of soil colloids decreases, alkalinity decreases, and the availability of nitrogen, phosphorus, potassium, and calcium for plants increases, while microbiological processes are activated [27][28][29][30][31]. At the same time, the application of gypsum limits or weakens alkalinisation processes only, but does not eliminate them completely [32,33].…”
Section: Introductionmentioning
confidence: 99%